Ethical Perceptions of Generation Z on Duped Products: The Role of Intellectual Property Awareness - Rolando Magat Jr; Arahvela Dungog; Laurence A. Castillo; Alyssa Kyla V. Cimacio; Ronafel C. De Los Reyes (Journal of Management Studies and Development, 2026)
The increasing prevalence of dupe products has raised ethical concerns, particularly among Generation Z, whose consumption behavior is shaped by affordability, social influence, and evolving moral standards. While prior studies have examined ethical consumption and intellectual property (IP) awareness separately, limited research explains how consumer-related factors translate into ethical perceptions through IP awareness. Addressing this gap, the present study investigates the ethical perceptions of Generation Z toward duped products by examining the relationships among consumer-related influencing factors, IP awareness, and ethical perceptions within a mediated framework. Employing a quantitative, descriptive–correlational design, data were collected from 400 Generation Z respondents in Metro Manila using a validated, researcher-made questionnaire. The data were analyzed using descriptive statistics, non-parametric correlation, and Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping. The findings reveal that consumer-related influencing factors significantly affect ethical perceptions both directly and indirectly through IP awareness, confirming a partial mediation effect. Although Generation Z demonstrates general awareness of IP rights and acknowledges ethical concerns, economic practicality and social normalization continue to shape ethical judgments. Anchored on Behavioral Reasoning Theory and Cognitive Dissonance Theory, the study contributes to a deeper understanding of ethically ambiguous consumption by highlighting how awareness interacts with consumer reasoning processes. The findings have implications for IP education, ethical marketing, and policy initiatives aimed at promoting responsible consumption. The study concludes that strengthening IP awareness alone is insufficient; ethical interventions must also address the economic and social contexts influencing Generation Z. Future research is recommended to explore longitudinal effects and cross-cultural perspectives on ethical consumption of dupe products.